Особливості підбору кадрів для ведення агітаційної кампанії - Нечиталюк, Влада; Марковець, Олександр (Видавництво Львівської політехніки, 2019)
This article analyzes how employers are goverment when selecting a candidate for agitation and what qualities candidates should have in order to conduct productive and highquality campaigning in any field.
Keywords: агітація; агітатор; вплив; спонукання; якості; соціальні мережі; кандидат